Assessing resource curse risks in namibia's green hydrogen developments with insights from diamond mining - Akuaake, Iyaloo (Department of Chemical Engineering, 2024)
The global shift towards a green economy has garnered momentum in various countries, propelled in good part by steep growth and falling prices of renewable energy. So-called ”green” hydrogen, derived from electrolysis of water at times and in places with excess renewable energy is expected to become a major clean energy carrier. , It holds the dual role of energy storage and supply, as well as decarbonizing challenging sectors such as aviation and maritime transport and steelmaking. Several countries with abundant wind and solar resources are envisioning to become major green hydrogen producers and exporters. Economic history, however, cautions against a high resource-sector dependence, with a well-developed literature on the resource curse. Namibia is one of these countries. This dissertation offers an exploratory assessment of resource curse risks which might emanate from Namibia's green hydrogen developments, focusing on the Southern Corridor Development Initiative. Drawing from historical experiences in the diamond sector, and building on institutional framework theory, the research examines the nuanced interplay between institutions and risks in the emerging green hydrogen industry. The study's objectives include assessing historical resource curse experiences in Namibia's diamond sector, identifying potential risks and their implications in the green hydrogen industry, and understanding the role of historical factors in shaping green hydrogen development. To achieve these objectives, the dissertation presents a mixed methods approach. The historical review utilizes secondary data sources to gather information on Namibia's diamond sector pre- and post-independence. The anticipatory part presents an expert elicitation, combining a survey with semi-structured interviews. The two parts are jointly analysed to offer quantitative and qualitative insights into the nuances of the green hydrogen industry and potential risks. The study acknowledges limitations related to the number of respondents and their willingness to participate but underscores the importance of the valuable insights provided by those who participated. The geographical scope of both parts focuses on the “Sperrgebiet” in Southern Namibia, with the diamond industry review being confined to onshore diamond operations in the southern region of Namibia, providing a focused examination while acknowledging the omission of marine diamond mining. Findings from the diamond sector analysis reveal a historical colonial curse rather than an economic resource curse. Post-independence, institutional shifts increased government ownership but left lingering socio-economic impacts unaddressed. Findings from the anticipatory study reveal that the green hydrogen industry faces potential resource curse risks, most likely concerning environmental impact, talent distribution challenges, expatriates dominating high-income jobs and more income inequality. The analysis suggests that the country's success with major green hydrogen industry ventures hinges on institutional responses to labor dynamics, environmental protection, and equitable economic benefits. Historical parallels underscore concerns about transparency, land concessions, and overexposure to a single dominating economic actor, calling for responsible industry development. The research highlights the importance of learning from past experiences to ensure sustainable development. The dissertation ends of with recommendations for future research and for practice.